EVALUATION OF DRUG USE PATTERN IN GYNECOLOGY DEPARTMENT USING WHO PRESCRIBING INDICATORS - P.HARSHA VARDHAN REDDY; V.RAVICHANDRAN; P.SHANMUGASUNDARAM (International Journal of Pharma and Bio Sciences, 2015)
To promote rational drug use, it is important to assess drug use pattern. The aim of this study was to evaluate the drug use patterns at the gynecology department. A prospective observational study was conducted over 6 months. The study sample size was 100 patients. The study concludes that patients aged between 35-50years (69%) are highly affected by gynecological diseases and abnormal uterine bleeding (38%) is the most common cause. Vitamin and mineral supplements are the highly prescribed drugs. The average number of drugs prescribed per encounter was 3.7. The percentage of encounters in which an antibiotic or injection was prescribed was 63% and 48% respectively. The Percentage of drugs prescribed by generic name and from an essential drug list was 83.8% and 78.4% respectively. On the finding of this study, the prescribing practices for drugs used in gynaecology department shows deviation from the standard recommended by the World Health Organization.